A Comparison of Handgun Shots, Balloon Bursts, and a Compressor Nozzle Hiss as Sound Sources for Reverberation Time Assessment - SZŁAPA, Piotr; BOROŃ, Marta; ZACHARA, Jolanta; MARCZAK, Wojciech (Archives of Acoustics, 2016)
Blank handgun shots, party balloon bursts, and a pneumatic compressor with a small-diameter nozzle were used as sources of sound in the assessments of reverberation time, $T$. The two first sources were of impulse type, while the third one resembled a noise signal source. In this work, 532 values of $T$ were experimentally obtained in four rooms of different volumes and compared. The $T$ values for 1/3 octave frequency bands were found to be independent of the sound source. Reverberation times for the A-frequency-weighting filtered signals were close to one another for the shots and balloon bursts, while those obtained using the compressor nozzle were significantly shorter. The latter effect can be attributed to the relatively high share of high frequency waves in the sound generated by the nozzle. The results show that balloon bursts can be used as handgun shot substitutes in the assessments of reverberation times. While the nozzle noise is rather unsuitable for this purpose, it can be applied in the assessments of $T$ for high frequency waves, up to the ultrasound range. Such acoustic climate information may be useful in designing spaces for high frequency sound-sensitive individuals, e.g. animal shelters.